A spin crossover (SCO) active graphene-iron(ii) complex hybrid material. Issue 1 (29th November 2017) - Senthil Kumar, Kuppusamy; Šalitroš, Ivan; Boubegtiten-Fezoua, Zahia; Moldovan, Simona; Hellwig, Petra; Ruben, Mario
Abstract : A graphene-spin crossover (SCO) complex hybrid (Gr-SCO-A), prepared by non-covalently anchoring a pyrene tethered iron(ii )-SCO complex1 with single/few layer graphene sheets, shows persistent thermal and light induced SCO. Abstract : The advancement of molecular electronics and spintronics requires novel hybrid materials with synergistic magnetic and electrical properties. The non-covalent functionalization of highly conductive graphene with magnetically bistable spin crossover (SCO) complexes may yield such a multifunctional material. In this regard, a graphene-Fe(ii ) SCO complex hybrid (Gr-SCO) has been prepared by non-covalently anchoring a pyrene decorated SCO complex with solution phase pre-exfoliated few-layer graphene sheets. SQUID magnetometry revealed the preservation of SCO in the Gr-SCO hybrid material exhibiting more gradual spin state switching characteristics than in the bulk molecular complex. This persistence of SCO of a molecular Fe(ii ) complex upon anchoring on the graphene surface has consequences towards the realization of SCO based applications: in (i) reversible spin state dependent band gap tuning of graphene with an SCO complex analogous to chemical doping of graphene, and (ii) to probe the spin state dependence of electrical conductivity modulation by wiring the anchoring group (pyrene) tethered SCO complex between chemically robust few-layer graphene electrodes.